Adsorption equilibrium and kinetics of CO2 on mesocellular foams modified HKUST-1: Experiment and simulation. Issue 44 (February 2021) - Zhao, Haihong; Zhao, Ning; Wang, Qin; Li, Feng; Wang, Feng; Fan, Subing; Matus, Ekaterina V.; Ismagilov, Zinfer R.; Li, Lei; Xiao, Fukui
Highlights: HK/MCFs-x composites were successfully synthesized. HK/MCFs-x composites exhibited good water resistance stability. The thermodynamics and kinetics of the HK/MCFS-1 were studied. The Langmuir-Freundlich model and pseudo-first-order equation could be used to describe the CO2 adsorption of the HK/MCFs-1. Abstract: In this work, a series of HK/MCFs-x sorbents consisting of metal organic framework (HKUST-1) and mesocellular foams (MCFs) were prepared using solvothermal method. The samples were characterized by various techniques including XRD, N2 adsorption/desorption, TG, SEM, FT-IR, and water vapor adsorption, respectively. The CO2 adsorption isotherms and adsorption kinetic curves at different temperatures were obtained. Results showed that the Langmuir-Freundlich model and pseudo-first-order equation could be used to describe the CO2 adsorption isotherms and kinetic curves, thus proving the exothermic, multilayer, physical adsorption processes. The isosteric heats of adsorption of the pure HKUST-1 and HK/MCFs-1 were in the range of 19–26 KJ/mol. The mass-transfer coefficient increased along with the temperature. The adsorption activation energies of the pure HKUST-1 and HK/MCFs-1 were 4.150 and 4.203 KJ/mol, respectively. Compared with the pure HKUST-1, HK/MCFs-1 had a substantially equivalent amount of CO2 adsorption capacity under the same conditions, while the water resistance was improved. The CO2 mass-transfer rate was higher than the pure HKUST-1. Meanwhile, HK/MCFs-1 also showed better recyclability.